2016
DOI: 10.1007/s40520-016-0559-9
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, diet quality, and mortality among sarcopenic older adults

Abstract: Background It is unknown if physical activity and good diet quality modify the risk of poor outcomes, such as mortality, among older adults with sarcopenia. Aim To examine if physical activity and good diet quality modify the risk of poor outcomes, such as mortality, among older adults with sarcopenia Methods A population-based cohort study among 1,618 older-adults with sarcopenia from the Third National Health and Nutrition Survey (NHANES III; 1988-1994). Sarcopenia was defined by the European Working Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Results of our current study are also consistent with our earlier study including older persons aged 65 years and older that was of shorter duration (mean follow‐up of 3.1 years) with fewer incident mortalities and found that low diet quality was associated with higher mortality risk . Other observational studies have also found that adherence to a healthy diet, assessed by the Healthy Eating Index (HEI), the Mediterranean diet score, and other indexes, was associated with lower risk of mortality in prefrail and frail older persons as well as older adults with sarcopenia . However, some studies examining the relationships between dietary pattern, diet quality, and mortality among older persons in observational studies revealed inconclusive results .…”
Section: Discussionsupporting
confidence: 91%
“…Results of our current study are also consistent with our earlier study including older persons aged 65 years and older that was of shorter duration (mean follow‐up of 3.1 years) with fewer incident mortalities and found that low diet quality was associated with higher mortality risk . Other observational studies have also found that adherence to a healthy diet, assessed by the Healthy Eating Index (HEI), the Mediterranean diet score, and other indexes, was associated with lower risk of mortality in prefrail and frail older persons as well as older adults with sarcopenia . However, some studies examining the relationships between dietary pattern, diet quality, and mortality among older persons in observational studies revealed inconclusive results .…”
Section: Discussionsupporting
confidence: 91%
“…24,25 In addition, physical activity and diet quality have been associated with reduced risk of CVD and mortality. 26,27 Levels of HbA 1c have been recognized as predictors of allcause mortality. 28 Both high and low levels of HbA 1c were associated with an increased risk of all-cause mortality in patients with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous quantitative reviews suggested that smoking, an established risk factor, has been proven to exert adverse effects on mortality . In addition, physical activity and diet quality have been associated with reduced risk of CVD and mortality . Levels of HbA 1c have been recognized as predictors of all‐cause mortality .…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of literature that recognizes the importance of physical activity in older people. It has previously been observed that engagement in physical activity has a positive impact on functional abilities [1,2], mobility [3], cognitive status [4,5], quality of life [6,7], risk of falls [8] and mortality [9,10]. In addition, the International Association of Gerontology and Geriatrics (IAGG) and the World Health Organization (WHO) have emphasized the importance of physical exercise in the quality of nursing home care [11].…”
Section: Introductionmentioning
confidence: 99%